Food Price Stabilisation and Food Security : International Experience - Dorosh, Paul A. (2012)
The importance of food commodities to consumers and farmers leads most countries to attempt to influence the levels and stability of food prices. The specific policies adopted and the degree of price stabilisation actually achieved vary considerably across countries, however. This paper reviews the experience of four countries (China, India, Bangladesh and Madagascar) that have implemented explicit price stabilisation and food security policies. Several policy lessons emerge from the analysis, including the potential savings to be made through reliance on international trade rather than buffer stocks; the likelihood of efficiency gains from relying more heavily on market mechanisms; the need to maintain transparency of policies; and the high cost of untargeted public distribution programs.